Origin of the different reactivity of the high‐valent coinage‐metal complexes [RCuiiiMe3]− and [RAgiiiMe3]− (R=allyl). Issue 7 (7th January 2022) - Auth, Thomas; Stein, Christopher J.; O'Hair, Richard A. J.; Koszinowski, Konrad
Abstract: High‐valent tetraalkylcuprates(iii ) and ‐argentates(iii ) are key intermediates of copper‐ and silver‐mediated C−C coupling reactions. Here, we investigate the previously reported contrasting reactivity of [RM iii Me3 ] − complexes (M=Cu, Ag and R=allyl) with energy‐dependent collision‐induced dissociation experiments, advanced quantum‐chemical calculations and kinetic computations. The gas‐phase fragmentation experiments confirmed the preferred formation of the [RCuMe] − anion upon collisional activation of the cuprate(iii ) species, consistent with a homo‐coupling reaction, whereas the silver analogue primarily yielded [AgMe2 ] −, consistent with a cross‐coupling reaction. For both complexes, density functional theory calculations identified one mechanism for homo coupling and four different ones for cross coupling. Of these pathways, an unprecedented concerted outer‐sphere cross coupling is of particular interest, because it can explain the formation of [AgMe2 ] − from the argentate(iii ) species. Remarkably, the different C−C coupling propensities of the two [RM iii Me3 ] − complexes become only apparent when properly accounting for the multi‐configurational character of the wave function for the key transition state of [RAgMe3 ] − . Backed by the obtained detailed mechanistic insight for the gas‐phase reactions, we propose that the previously observed cross‐coupling reaction of the silver complex in solution proceeds via the outer‐sphere mechanism. Abstract : Gas‐phase fragmentation experiments reveal a contrasting reactivity of the high‐valent coinage‐metal complexes [RCu iii Me3 ] − and [RAg iii Me3 ] − (R=allyl). Using DFT, coupled‐cluster and multi‐configurational calculations together with kinetic modeling, the reactivity difference is traced back to different C−C coupling propensities of the two complexes. For [RAgMe3 ] −, an outer‐sphere cross‐coupling transition state featuring a large multi‐configurational character plays a key role for the understanding of its reactivity.